Correlation Between Pre-Service Science Teacher Laboratory Self-Efficacy And Science Process Skills In Laboratory Activities - Yeni Widiyawati; Dwi Septiana Sari (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
Laboratory self-efficacy and science process skills are the key variables that need to be measured to show it’s a correlation. These variables will determine their career as a science teacher. Pre-service science teacher must have the skills to explain the natural objects and phenomena holistically and integrative. So that, the aims of this research was to 1) reveals the laboratory self-efficacy of, 2) identify science process skills level of and 3)identify the correlation between laboratory self-efficacy and science process skills of pre-service science teacher under laboratory activities. Quantitative-descriptive, scanning models were used to collect the data. Laboratory self-efficacy scale was developed of level, strength, and generality components. Documentation and observation techniques were used to collect the science process skills data. Bandura’s theory was adopted in self-efficacy Laboratory self-efficacy scale. Mean of laboratory self-efficacy of pre-service science teachers were in moderate level while their science process skills were at a low level. Spearman Rank test showed a significant correlation between these two variables. In the other hand. Regression test showed that laboratory self-efficacy does not significantly determine the pre-service science teacher science process skills’.